Using IoT System for Borrowing and Returning of Teaching Equipment in the Electrical Field - Chatwaranon, Yutti; Chatchawankitkun, Mallika; Srisathit, Sutthikiat; Yutthanaboon, Sathisn (วารสารวิทยสารสนเทศและเทคโนโลยี, 2025)
This study focuses on addressing the problem of equipment loss within the electrical engineering department at the Faculty of Electrical Engineering, Bangkok Thonburi University. The research objectives are twofold: (1) to develop and assess an application that utilizes LINE Notify for real-time notifications, integrating data collected through Google Forms; and (2) to create a system for storing borrower information using Google Sheets as the database, which allows for effective tracking and verification of equipment usage. Testing of the system demonstrated that it successfully records equipment borrowing through Google Forms and securely stores this information in Google Sheets for administrative oversight. The system provides timely notifications and detailed updates via LINE Notify, enabling administrators to approve borrowing requests through web browsers and applications. The results indicate that this system effectively mitigates equipment loss and enhances monitoring and management efficiency.